The Emerging Role of Non-Coding RNAs in Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells - Chen, Xiaoying; Xie, Wei; Zhang, Ming; Shi, Yuhan; Xu, Shaofen; Cheng, Haoyu; Wu, Lihong; Pathak, Janak L.; Zheng, Zhichao (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) retrieved from bone marrow, cartilage, adipose, tendon, dental tissues, and periosteum are commonly used for bone regeneration and bone tissue engineering applications. Autologous bone marrow-derived mesenchymal stem cells (BMSCs) are more easily available and frequently used for bone regeneration in clinics. Osteogenic differentiation of BMSCs involves complex regulatory networks affecting bone formation phenomena. Non-coding RNAs (ncRNAs) refer to RNAs that do not encode proteins, mainly including microRNAs, long non-coding RNAs, circular RNAs, piwi-interacting RNAs, transfer RNA-derived small RNAs, etc. Recent in vitro and in vivo studies had revealed the regulatory role of ncRNAs in osteogenic differentiation of BMSCs. NcRNAs had both stimulatory and inhibitory effects on osteogenic differentiation of BMSCs. During the physiological condition, osteo-stimulatory ncRNAs are upregulated and ostoe-inhibitory ncRNAs are downregulated. The opposite effects might occur during bone degenerative disease conditions. Intracellular ncRNAs and ncRNAs from neighboring cells delivered via exosomes participate in the regulatory process of osteogenic differentiation of BMSCs. In this review, we summarize the recent advances in the regulatory role of ncRNAs on osteogenic differentiation of BMSCs during physiological and pathological conditions. We also discuss the prospects of the application of modulation of ncRNAs function in BMSCs to promote bone tissue regeneration in clinics.